ISOLATION AND IDENTIFICATION OF FLAVONOIDS FROM Sesamum indicum - Priyanka Sharma; Renu Sarin (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Natural substances have long served as sources of therapeutic drugs. Many substances have been derived from traditional medicines. The plants are rich in secondary metabolites. The medicinal properties of these plants have been attributed to the biochemicals present in the plant materials. In addition to their role in human and animal nutrition, knowledge of micronutrients and phytochemical composition is fundamental to the understanding of modes and mechanisms of action of medicinal plants in general. In the present investigation, quercetin and kaempferol have been isolated and identified from stem, leaves and unorganized cultures of Sesamum indicum and maintained by frequent subculturings on Murashige and Skoog’s medium (1962) supplemented with NAA+BAP(5.0+0.5mg/L). The study showed that maximum content of quercetin and kaempferol was observed in 6 weeks old calli and minimum in stem of S. indicum. The structure of the isolated compound was established on the basis of physical, chemical test and spectroscopic evidences.Key words: Flavonoids, quercetin, kaempferol, Sesamum indicum